Aesthetic Study of Temple Architecture in Bali: A Case Study of Pamesuan Pura Puru Sada, Pura Agung Kentel Bumi, and Pura Batuan - Made Wina Satria; Km Deddy Endra Prasandya (Program Studi Arsitektur, Fakultas Teknik dan Perencanaan, Universitas Warmadewa, 2024)
A temple as a place of worship is a sacred building, the center of worship of Ida Sang Hyang Widhi Wasa (God Almighty for Hindus) and His manifestations, so that its placement is in a part that is considered main in the land plan of a village or other special place according to applicable local village regulations. In the construction and planning, determining the size, layout, as well as the meaning and symbolism of each temple building in Bali has been stated in the lontar Asta Kosala. Meanwhile, the land management is stated in lontar Asta Bumi. Even though it was built based on concepts from the same lontar source, the shape and appearance of each temple can be very different. Each region in Bali has a unique architectural style, both in ornamentation, use of materials, and even the proportions of the form. In the view of Balinese architecture, the assessment of aesthetic quality is more focused on meaning, taste, and philosophical values, so the assessment tends to be subjective. This research seeks to examine the relationships between humans and the environment, especially those related to aesthetic aspects. The research method used is interpretive criticism, which is not influenced by certain views or doctrines and does not base itself on measurable objectivity. The results of the research show that there is an influence of formal aesthetics on the sensory and symbolic, where the shape and dimensions of the gates (both Candi Bentar and Kori Agung) have given an aesthetic impression to observers, which is then captured by visual sensors and interpreted.